PEMANFAATAN LAHAN TERBENGKALAI UNTUK MENCETAK PROFITABILITAS UMKM - CIMANUK- PANDEGELANG - Sultan Antus Nasruddin Mohammad; Muzayanah (LPPM STAI Muhammadiyah Probolinggo, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy, yet they face significant structural challenges, particularly the limited access to productive land. This article analyzes the potential, challenges, and strategies for utilizing abandoned land to enhance MSME profitability, based on a participatory case study in Cimanuk District, Pandeglang. This study employed a qualitative approach with data collection techniques including in-depth interviews, participant observation, and Focus Group Discussions (FGDs). The findings indicate that abandoned land possesses significant potential as a community asset that can be activated for productive economic activities such as hydroponic agriculture, medicinal plant cultivation, and local crafts. However, its utilization is hampered by systemic barriers, including limited access to finance, low technical skills, complex regulatory hurdles, and inadequate infrastructure. The research concludes that overcoming these challenges requires an integrated, multi-stakeholder collaborative strategy involving local government, financial institutions, and the community. The Cimanuk model demonstrates that activating underutilized local assets not only increases MSME income by up to 30% but also contributes directly to achieving Sustainable Development Goals (SDGs), particularly those related to poverty reduction, food security, and decent work.